The Decolonial View of Management (GESTIÓN Y TENDENCIAS, 2018)
Traditional management theory, researched and taught in most business schools, has drawn a variety of criticisms in academic circles. One of these is inspired by the "decolonial" approach, which challenges theories that are replicated and disseminated around the globe without adequately considering the context in which they are applied. This decolonial view seeks to make evident the process of colonization of knowledge that accompanies the expansion of management, and with it the second place to which our scant production of knowledge is relegated and its consequent practice.